Impelementation of Local Tax Billing at The East Kalimantan BAPENDA - Faris, Nabil Nurrahman; Fitriandi, Primandita (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
This study aims to determine the guidelines for implementing tax collection and explain the flow of tax collection at the Regional Revenue Agency of East Kalimantan Province. In addition, this study seeks the implementation of tax collection carried out in Bapenda East Kalimantan and provides suggestions and alternatives that need to be considered. This research uses a qualitative approach with field research analysis studies. Data collection was carried out using literature method and interviews. Finding shows that the implementation of tax collection in Bapenda East Kalimantan is quite good with the issuance of Regional Tax Bills. However, the absence of a tax bailiff results in the absence of issuance of Forced Letters to taxpayers who have tax bills that have passed the time period. Determination of Regional Regulations related to tax collection and training of tax bailiffs to be considered by the East Kalimantan Provincial Government so that tax collection and tax revenue are maximized.